Implementing TPACK-Based Technology Integration Training for Pre-Service Teachers in the Philippines - Aziez, Feisal; Sadeli, Elly Hasan; Furqon, Miftahul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This study analyses the conduct and results of a technology-integrated pedagogical training program for pre-service teachers in Gabaldon Municipality, Nueva Ecija Province, Philippines. The program aimed to capacitate future teachers with digital competencies and knowledge of specific pedagogical strategies anchored in the Technological Pedagogical Content Knowledge (TPACK) framework. This research utilized a mixed-methods approach, combining survey instruments, interviews, and classroom observations to determine how the training effectively enhanced readiness to integrate technology into one's teaching practice. The findings suggest marked improvements in the participants' TPACK domains, increased confidence in using educational technologies, and a favorable attitude toward integrating technology into their classes. This study recommends developing contextualized, comprehensive, and targeted training programs to propel pre-service teachers into embracing the demands of contemporary classrooms.